An evaluation of financial losses due to lumpy skin disease outbreaks in dairy farms of northern Thailand - Modethed, Wittawat; Kreausukon, Khwanchai; Singhla, Tawatchai; Boonsri, Kittikorn; Pringproa, Kidsadagon; Sthitmatee, Nattawooti; Vinitchaikul, Paramintra; Srisawang, Supitchaya; Salvador, Roderick; Gubbins, Simon; Limon, Georgina; Punyapornwithaya, Veerasak (Frontiers in Veterinary Science, 2025)
Lumpy skin disease (LSD) poses a significant threat to the cattle industry, resulting in adverse economic consequences in affected countries. This study aims to estimate the financial losses due to LSD outbreaks in dairy farms in northern Thailand. Based on a retrospective study, data was collected using a standardized questionnaire from 100 farms affected by LSD outbreaks (outbreak farms) and 33 farms that did not experience LSD outbreaks (non-LSD outbreak farms) in two dairy farming areas that experienced LSD outbreaks between June and December 2021. In outbreak farms, the average total financial losses was 727.38 USD per farm, significantly higher than the 349.19 USD per farm observed in non-LSD outbreak farms. The primary cause of financial loss in outbreak farms was mortality. Reductions in milk sold due to a drop in milk production, and the need to discard milk because of the withdrawal time of antibiotics used for treating secondary infections on affected cattle, also contributed substantially to the financial losses. On farms without LSD outbreaks, the main expenses were related to vaccination and disease prevention, amounting to 130.66 USD and 218.53 USD per farm, respectively. LSD outbreaks negatively affect all farms in the outbreak areas, as both outbreak farms and non-LSD outbreak farms had to bear prevention costs. In the post-outbreak phase, the primary activities focused on continued monitoring of new LSD cases and conducting surveillance, carried out collaboratively by farmers and livestock authorities. This is the first study in Thailand providing valuable insights into the financial implications of LSD outbreaks for farmers, highlighting the substantial financial consequences of the disease. The findings from this study are beneficial for decision making, efficient resource allocation and the development of effective mitigation strategies.